Association of thyroid peroxidase antibodies with the rate of first-trimester miscarriage in euthyroid women with unexplained recurrent spontaneous abortion - Liu, Meilan; Wang, Dongyan; Zhu, Liqiong; Yin, Jianlan; Ji, Xiaohui; Zhong, Yilei; Gao, Yuan; Zhang, Jianping; Liu, Yukun; Zhang, Rui; Chen, Hui (Frontiers in Endocrinology, 2022)
Abstract Background: Unexplained recurrent spontaneous abortion is a serious reproductive problem of unknown etiology. Thyroid peroxidase antibodies (TPO-Ab) may be associated with pregnancy outcomes in unexplained recurrent spontaneous abortion with normal thyroid function. Objective: This study aimed to investigate the relationship between TPO-Ab and the first trimester miscarriage rate /live birth rate in women of unexplained recurrent spontaneous abortion with normal thyroid function. Methods: We retrospectively analyzed the clinical data of 297 women who met our strict inclusion criteria, comparing the first trimester miscarriage rate /live birth rate between the TPO-Ab positive and TPO-Ab negative groups. For the same purpose, we also performed subgroup analysis. Results: Of the included women, 76 (25.6%) were TPO-Ab positive, and 221 (74.4%) were negative. First trimester miscarriage rate differed between the two groups (36.8% vs 24.0%, RR = 1.54, 95% CI: 1.05–2.24, P = 0.030). In the younger subgroup (<35 years) and the primary RSA subgroup, First trimester miscarriage rate was also higher in the TPO-Ab positive group (33.3% vs 19.0%, RR = 1.75, 95% CI: 1.07–2.87, P = 0.030; 36.5% vs 21.7%, RR = 1.69, 95% CI: 1.10–2.58, P = 0.020). While the live birth rate was lower in women with TPO-Ab positive, the difference did not reach statistical significance, even in the subgroup analysis. Conclusion: Our results suggest that TPO-Ab is associated with first trimester miscarriage rate in euthyroid women with unexplained recurrent spontaneous abortion.